Penentuan Strategi Optimal Dengan Game Theory Pada Persaingan 3 Kuliner Bakso Di Galuh Mas Karawang - Harun, Muhammad; Suseno, Agustian (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
The culinary area located in Galuh Mas Karawang is a strategic area that is very busy and never empty of visitors. The purpose of this study was to determine the optimal strategy between the three meatball with chicken noodle culinary competitions, namely Baso Ambon, Baso Malang and Baso Sopo Nyono. The research sample was 167 respondents who were only visitors and direct customers from the three meatball culinary places in March 2021. Based on the results of data processing with this method, it is found that the optimal strategy between Baso Malang and Baso Ambon has a meeting point of maximum value equal to the minimum value called a saddle point of 0.067 on row X2 and column Y1 which means Baso Malang uses a better service strategy than Baso Ambon. Meanwhile, Baso Ambon uses a more affordable price strategy than Baso Malang. Then for Baso Sopo Nyono and Baso Ambon have a saddle point of 0.284 on row X3 and column Y1, meaning that Baso Sopo Nyono uses a more complete facilities strategy than Baso Ambon.